The Effectiveness of Live Worksheets-Assisted Problem Based Learning to Improve Students’ Mathematical Problem Solving Abilities - Wardani, Dina Syafitri; Sugandi, Asep Ikin ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2024)
This research was motivated by the low mathematical problem solving ability of students based on the results of field observations and the results of previous research. This study aims to determine the effectiveness of LKPD assisted by live worksheets with a problem-based learning approach to the mathematical problem solving ability of grade VIII students. The method used in this study is an experimental method with One-Group Pretest-Posttest Design by Sugiyono. The subjects in this study were 30 grade VIII students at MTs Al-Firdaus with low, medium to high categories. The research instrument used in this study was in the form of five description questions adjusted to indicators of problem-solving ability which were then calculated using the SPSS application. Based on the calculation of the comparison of pre-test and post-test values, it is found that the post-test value is greater than the pre-test value. In the pre-test students still have some errors in working on the problems given, while during the post-test few students make mistakes in solving problems. Based on the research conducted, it can be concluded that LKPD assisted by live worksheets with a problem-based learning approach is effective in improving the mathematical problem solving ability of grade VIII students, especially on the Pythagorean theorem material.